Strengths and weaknesses of pneumococcal conjugate vaccines - Micoli, Francesca; Romano, Maria Rosaria; Carboni, Filippo; Adamo, Roberto; Berti, Francesco (Glycoconjugate journal, 2023)
Multivalent vaccines addressing an increasing number of Streptococcus pneumoniae types (7-, 10-, 13-, 15-, 20-valent) have been licensed over the last 22 years. The use of polysaccharide-protein conjugate vaccines has been pivotal in reducing the incidence of invasive pneumococcal disease despite the emergence of non-vaccine serotypes. Notwithstanding its undoubtable success, some weaknesses have called for continuous improvement of pneumococcal vaccination. For instance, despite their inclusion in pneumococcal conjugate vaccines, there are challenges associated with some serotypes. In particular, Streptococcus pneumoniae type 3 remains a major cause of invasive pneumococcal disease in several countries. Here a deep revision of the strengths and weaknesses of the licensed pneumococcal conjugate vaccines and other vaccine candidates currently in clinical development is reported.